Grundsteuer. Die Qual der Wahl. - Zimmermann, Horst (Springer, 2019)
Durch die nun beschlossene Reform der Grundsteuer wird das völlig neue Element einer Länder-Öffnungsklausel eingeführt. Die Länder müssen entscheiden, ob sie den Vorschlag des Bundesfinanzministeriums oder eine der anderen Reformoptionen wählen. Deren Vor- und Nachteile werden damit sehr wichtig. Der Beitrag stellt vier relevante Modelle gegenüber und bewertet sie unter dem Aspekt einer "guten" Gemeindesteuer.

The reform of the German property tax, which has now been agreed upon, introduces the brand new element of a state opening clause. German states must now decide whether to accept the proposal of the Federal Ministry of Finance or one of the other reform options. The advantages and disadvantages of these options, therefore, become very important. The article compares four relevant property tax models and assesses them from the point of view of a 'good' municipal tax.
Keywords: Steuer; Grundsteuer; Steuerreform; Gemeinde; Auswahlverfahren